Resource Use Efficiency Analysis for Potato Production in Nepal - Sapkota, Mahesh; Bajracharya, Mahima (Journal of Nepal Agricultural Research Council, 2018)
Potato is one of the most important staple foods supporting food security and livelihood to millions of marginalized and poor farmers in Nepal. Generally the smallholders’ farmers, especially those located in remote villages are inadequately informed about technical knowledge, inputs and efficient use of resources causing poor production and low productivity. Thus, the present survey aimed to examine the efficiency of resources used in potato production in Baglung District, one of the remote hilly place located in Central Himalaya. The total of 120 potato growing households was selected using simple random sampling technique from the two potato pocket in 2016. The regression coefficients of each inputs using Cobb-Douglas production function were estimated using Stata software. Our results showed that major inputs such as labor, bullock, Farm Yard Manure (FYM) and intercultural operations were overused and need to decrease in terms of cost by 109, 177, 51 and 185%, respectively for its optimum allocation. Similarly, seed was found underused and need to increase its cost by 70% for optimum allocation. We concluded that inadequate training, exposure, knowledge gap and extension service to farmers in study sites were the reasons that farmers were using their resources inefficiently. It is recommended that the farmers involved in potato farming in the surveyed sites should be provided with additional proper technical knowledge for optimizing the use of resources which would help to increase the production and return from potato production.